Using the concept of encounter to further the social inclusion of people with intellectual disabilities: what has been learned?. Issue 1 (2nd January 2019) - Bigby, Christine; Wiesel, Ilan
Abstract: Social inclusion has been an enduring policy aim of intellectual disability policy since the early 1980s, which has been difficult to achieve. It has often been conceptualised as the binary between social presence or social participation. This article synthesises the findings from a program of Australian research that explored the application of "encounter" and "conviviality" – concepts from urban geography, as lenses for understanding the types of places, activities, and practices that facilitate or obstruct social inclusion of people with intellectual disabilities. Three types of convivial encounter were identified: moments of shared identification, everyday recognition, and becoming known. Most common were fleeting convivial encounters of everyday recognition in public places or commercial premises. Convivial encounters were facilitated by: places where activities were non-competitive, there was a shared purpose for being there and opportunities for spoken and other forms of communication; community members' with experience, confidence, or comfort in interacting with people with intellectual disabilities; and skilled judgments and assistance from support workers in the moment, and their decisions about use of non-segregated mainstream places. The final part of the article reviews studies by other disability studies researchers, who using ideas about encounter have found that the presence of a dog, and places where there is clarity about rules and roles, are facilitating factors, and have begun to investigate more systematic ways of creating opportunities for convivial encounters through social enterprises, community groups, classes, and volunteering.